Optimalisasi Pemanfaatan E-Money Dalam Meningkatkan Efektivitas Dan Efisiensi Transaksi Santri Pondok Riyadlul Jannah Pacet - Imam Wahyudi; Nia Kurniasih (FADZAT: Jurnal Ekonomi Syariah, 2025)
The rapid development of digital financial technology has encouraged Islamic boarding schools to adopt non-cash payment systems, including electronic money (e-money), to support efficient and transparent financial management. This study aims to analyze the optimization of e-money utilization in enhancing the effectiveness and efficiency of students’ transactions at Riyadlul Jannah Islamic Boarding School, Pacet, Mojokerto, while examining its compliance with Islamic economic principles. This research differs from previous studies by focusing not only on the implementation of e-money but also on its optimization strategy and integration with Islamic values and character education. Using a qualitative descriptive approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation involving students, parents, and boarding school administrators. The findings reveal that e-money significantly improves transaction speed, accuracy, security, and convenience, while increasing financial transparency and accountability. From an Islamic economic perspective, e-money implementation is considered permissible as long as it avoids riba, gharar, and maysir, and upholds the principles of amanah, justice, efficiency, and maslahah. This study implies that optimizing e-money in Islamic boarding schools can function not only as a technical payment instrument but also as a medium for Islamic financial literacy and character building